2015
DOI: 10.5812/ircmj.16823
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ureaplasma urealyticum and Mycoplasma hominis in High Vaginal Swab Samples of Infertile Females

Abstract: Background:Mycoplasma hominis and Ureaplasma urealyticum are important causative agents of vaginitis, cervicitis, postpartum sepsis, reproductive infections and infertility in both males and females.Objectives:According to the uncertain prevalence of U. urealyticum and M. hominis in Iranian infertile females, the present study was carried out to determine the prevalence of U. urealyticum and M. hominis in high vaginal swab samples of fertile and infertile females.Patients and Methods:A total of 350 high vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Forty-four original articles (full texts) related to prevalence of M. genitalium, M. hominis, and U. urealyticum in Iranian men and women in our literature review remained for reviewing and assessing for eligibility criteria. The final 44 articles were included: M. genitalium [17], M. hominis [18], U. urealyticum [19] with some of them contains two [15] or three [2] of these bacteria ( Fig. 1).…”
Section: Description Of Included and Excluded Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-four original articles (full texts) related to prevalence of M. genitalium, M. hominis, and U. urealyticum in Iranian men and women in our literature review remained for reviewing and assessing for eligibility criteria. The final 44 articles were included: M. genitalium [17], M. hominis [18], U. urealyticum [19] with some of them contains two [15] or three [2] of these bacteria ( Fig. 1).…”
Section: Description Of Included and Excluded Studiesmentioning
confidence: 99%
“…Despite the worldwide incidence of genital mycoplasmas infections, there are no accurate reports of prevalence, common types, common routes of transmission and antibiotic resistance patterns of M. genitalium, M. hominis and U. urealyticum in Iran [17]. There are some studies about the presence of genital mycoplasmas among men, women, pregnant, newborns, infertile and etc in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies in the Italian population have reported a higher prevalence of U. urealyticum and M. hominis, and a possible association of M. hominis with bacterial vaginosis. [16][17][18][19][20] In some patients, we observed coinfection of Ureaplasma spp. with M. hominis, which is expected.…”
Section: Discussionmentioning
confidence: 99%
“…hominis and/or Ureaplasma spp. was 2.4-fold higher in vaginal swabs of infertile women (n = 150) than of fertile women (n = 200) [ 17 ]. Olomu et al published in 2009 that the presence of ureaplasma in placental tissue before 28 gestational weeks was associated by a higher risk of preterm birth and neonatal complications such as intraventricular hemorrhage, inflammation and brain lesions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%